Concentração de colágeno na pele facial de mulheres na pós-menopausa após tratamento com estradiol e genisteína tópicos: um estudo randomizado duplo cego - Sampaio, Lidia Lima Aragao [UNIFESP] (2016)
Objective: To compare the known effects of estrogen with genistein on the facial skin collagen of postmenopausal women without hormone therapy. Methods: This is a clinical, cross over trial with randomized and blinded convenience sample with estrogen and isoflavones, which 30 volunteer postmenopausal women were recruited to quantify facial collagen concentration before and after topical use of estrogen and isoflavones for 24 weeks. Results: The amount of both types I and III collagen increased at the end of both treatments, but estrogen was superior to the phytoestrogen, with statistical significance. Conclusion: Treatment with topical estrogen is superior to phytoestrogen, but both showed an increase in facial skin collagen, with statistical significance. What is not yet clear is whether prolonged topical use of such substances can cause systemic effects, thus, more research is needed to clarify this question.